Off-farm labor supply decision of adults in rural Ethiopia: double hurdle approach - Bedemo, A.; Getnet, Kindie; Kassa, B.; Chaurasia, S.P.R. (2013)
This article examined the determinants of off-farm labor supply decision of adult members of households in rural western Ethiopia using cross-section data collected from 324 sample households. The double hurdle model was employed and the off-farm work participation and hours of work decision of male and female adults were jointly estimated. The result indicated that individual characteristics, household composition, availability of credit, value of off-farm equipment and location factors significantly influenced participation decision; yet, individual attributes, economic incentives and location were the major determinants of hours of work decisions. The findings imply that given the importance of off-farm activity in alleviating the problems of low agricultural productivity and the resulting low income, policy measures which can promote rural investment and create employment opportunities in off-farm activities may help minimize the effects of low farm income.